Electrical safety in the laboratory - Sanger, John M.; The MARCOM Group, Ltd. (Boothwyn, PA : The MARCOM Group, Ltd., 1993)
Labs rely on a vast array of electrically powered equipment. To work safely with this equipment employees need to know how electricity works and the dangers it holds. Principles of electrical energy, fuses, short circuits,'Lock- Out/Tag-Out', and instrument repair are covered
Title from title screen
Executive producer, Donald L. Leonard
Keywords: Chemical laboratories -- Safety measures; Electricity -- Safety measures; Accidents -- Prevention; Laboratories